The application of ketorolac in the prehospital treatment of renal colic - case report and literature review - Janković Tamara; Vukićević Verica; Đorđević Stefan (Halo 194)
Introduction/Objective: Renal colic (RC) presents as severe pain with sudden onset in the costovertebral angle of the corresponding side, radiating towards the inguinal area. The most common cause is urolithiasis. The clinical presentation is usually a sudden, unilateral onset of severe pain located in the lumbar region, accompanied by nausea or vomiting and dysuria, a frequency of urination with only a small amount of urine passed each time. The diagnosis is made based on patient history, clinical examination, urine sediment analysis, abdominal ultrasound and plain X-ray imaging of the urogenital tract (UGT). In this paper, we present the case of a patient suffering from a sudden onset of RC due to a previously undiagnosed urolithiasis, and the prehospital pharmacological treatment with a discussion about the wide range of drugs that can be administered. Case report: The Institute for Emergency Medicine Belgrade Call Centre received a medical emergency call for a patient suspected of suffering from renal colic. The 28-year-old woman reported that she had felt sudden, severe pain in the left flank propagating towards the groin area, accompanied by nausea and sweating. After taking an Ibuprofen tablet, the intensity of the pain decreased. On examination, Murphy's punch sign was positive on both flanks, although the reaction was more pronounced on the left side. Under the working diagnosis of RC caused by urolithiasis, the patient was transported to the hospital. She received 30mg of Ketorolac and 20mg of Hyoscine-butylbromide IV during transport. Ten minutes later, the intensity of the pain decreased, and by the time they arrived at the hospital, the pain had completely stopped. Conclusion: Ketorolac is a very effective analgesic when treating RC. Studies have shown that it has a stronger analgesic effect than opioids. When treating RC in the prehospital setting, the choice and the dose of drugs should be adjusted individually for each patient.